UZBEK PEOPLE’S DEMONOLOGICAL BELIEFS (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the demonological beliefs of the Uzbek people as an integral component of their traditional worldview and spiritual culture. It analyzes mythological and folkloric representations of supernatural beings such as jinn, pari (fairy spirits), alvasti, and other invisible entities within oral traditions, legends, ritual practices, and everyday beliefs. The study explores the dualistic perception of benevolent and malevolent spirits, their symbolic functions, and their role in explaining unexplained natural and social phenomena. Particular attention is given to the interaction between pre-Islamic mythological layers and later Islamic interpretations, revealing the continuity and transformation of demonological concepts in Uzbek cultural consciousness. The research highlights how these beliefs reflect moral norms, social values, and collective identity within traditional society.
Keywords: Uzbek demonology, folk beliefs, jinn, pari, mythology, folklore, traditional worldview, spiritual culture, dualism, oral tradition.